Development of Educational Innovation Through Learning Media - Sukma Ayu Kharismawati (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
The development of educational innovations is carried out systematically and comprehensively. One of them is by utilizing learning media. Various learning media can function as a solution to learning problems. However, the reality is not following these ideal conditions. This condition could cause the results of a study that achieved student disappointment. One of the problems schools face is the use of learning media which is not optimal enough. Study this using approach descriptive qualitative with type literature review. The destination of using this method is to serve various theories from previous researchers or experts relevant to the problem researched to help discuss the study's results in descriptive form. Teachers make learning breakthroughs so that students can learn with pleasure. Applying innovation education as learning means creating study patterns, working, and training independently following interest and talent learners. This innovation can be implemented through the use and application of learning media in schools using environment-based media. Learning media as part of educational innovation is essential for human resources and the future of Indonesia. SDN Remo is a small elementary school with all its limitations, trying to choose and utilize learning media from the natural environment so that students will quickly understand the subject matter.